Can the Subaltern Play and Speak or Just be Played With? - Leonard, David J. (Handbook of Research on Effective Electronic Gaming in Education, 2009)
This chapter examines and responds to the silencing, resistance to any intrusion of questions about race and racism, and overall erasure of race from the debates and broader discourse concerning video game culture. It not only provides insight into the nature and logics guiding claims of colorblindness, but also connects the ideologies and culture of denial to the broader racial discourse of post-civil rights America. Hoping to inspire debate and transformative knowledge sharing, this chapter additionally offers a textually-based racial analysis of Outlaw Volleyball as an example of the type of critical examination required to move beyond a culture that often reduces bodies and voices of people of color to objects of gaze, ridicule, and consumption while denying any sorts of criticism and questions regarding the racial meaning and texts evident within much of today’s gaming.
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

Gender and Racial Stereotypes in Popular Video Games - Mou, Yi; Peng, Wei (Handbook of Research on Effective Electronic Gaming in Education, 2009)
While the violent content of video games has caused wide concern among scholars, gender, and racial stereotypes in video games are still an understudied area. The purpose of this chapter is to provide a better understanding of the stereotypical phenomenon in video games. The book chapter first provides a comprehensive review of previous studies conducted upon gender-role and racial portrayals in video games. Then a small-scale content analysis on a sample of official trailers, introductory sequences and covers of 19 of the most popular video games is introduced. Finally, the implications of stereotype in video games and the possible social and psychological impacts on players, especially adolescent players, are discussed.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude de la réception; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé